Biological control of maize sheath blight caused by Rhizoctonia solani using rhizosphere fungi isolated from wild Solanum lasiocarpum Dunal: an in vitro study - Rahmawati Budi Mulyani; Yanetri Asi Nion; Adrianson Agus Djaya; Kambang Vetrani Asie; Rangga Rangga; Putri Lestari (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Maize sheath blight caused by Rhizoctonia solani is a major constraint to maize production, particularly in tropical peatland ecosystems where environmental conditions favor pathogen development. This study evaluated the antagonistic potential of rhizosphere fungi isolated from the indigenous plant Solanum lasiocarpum Dunal (Terung Asam) against R. solani under in vitro conditions. Rhizosphere fungi were isolated and identified using morphological characteristics and ITS rDNA sequencing, while their antagonistic activity and volatile organic compound (VOC)-mediated inhibition were assessed using dual culture and sealed plate assays. Six fungal isolates were successfully recovered from the rhizosphere of S. lasiocarpum and identified as belonging to the genera Trichoderma (TA-1–TA-3) and Aspergillus (TA-4–TA-6). Among them, Trichoderma isolate TA-1 (82.8%) and Aspergillus isolate TA-4 (81.4%) exhibited the highest inhibition of R. solani, indicating strong antagonistic activity through competition, mycoparasitism, and antibiosis. In the VOC assay, Aspergillus isolates TA-4 and TA-5 showed the strongest inhibition of pathogen growth, suggesting the production of antifungal volatile metabolites. Molecular identification based on ITS sequencing and BLAST analysis confirmed that isolate TA-1 was Trichoderma asperellum (576 bp) and isolate TA-4 was Aspergillus welwitschiae (574 bp), both sharing 100% sequence similarity with reference sequences in GenBank. To our knowledge, this is the first report describing antagonistic fungi isolated from the rhizosphere of wild S. lasiocarpum as potential biological control agents against maize sheath blight caused by R. solani. These indigenous fungi represent promising candidates for the development of environmentally sustainable disease management strategies in tropical peatland agriculture.